Person in the World : Introduction to the Philosophy of Edith Stein - Baseheart, Mary Catharine (Contributions to Phenomenology, In Cooperation with the Center for Advanced Research in Phenomenology, 1997)
The guideline that runs through all [Stein's] work is the inquiry into the question of the nature of the human person. Beginning with her dissertation on empathy and following through to the works of her maturity, the reader becomes aware of the thrust toward revealing the person as person, in its universality, transcending time and place and cultural milieu. Stein holds that phenomenology supplies the most effective means towards arriving at knowledge of what it means to be a person, and that phenomenological analysis can reveal the essential constitution of human-being-in-the-world ... My purpose in this book is to remove the wrapping and lid from the gift that Edith Stein has given us and to say: `Look! See what is inside.' In a first attempt in English to do this in a comprehensive way ... I have indicated the need for ongoing study and critique.